FEATURES, SIMILARITIES AND DIFFERENCES OF PHYTONYMIC PHRASEOLOGY IN ENGLISH AND UZBEK LANGUAGES - Matkarimova Gulira'no Abdullayevna (Journal of new century innovations, 2024)
Plants - create a living environment for a person and provide him with everything necessary for living. That is why flora represents an important part of the linguistic picture of the world. The participation of phytonyms in the formation of the linguistic picture of the world is multifaceted. Linguistic-cultural study of phytonyms allows us to gain a certain understanding of the various linguistic phenomena of a particular nation. So, the phraseological units that we have considered, which have a phytonymic component in their composition, allow us to draw a conclusion about the general concept. In this article, while studying phraseological units in English and Uzbek languages, we will compare them and consider their similarities and differences.